BELITUNG: Mathematics Learning Media for Grade III Elementary School - Rahmawati, Ulfah Dewi; Amalia, Nur (LPPM Undiksha, 2023)
The concept of adding and subtracting integers is a concept that absolutely must be mastered by anyone who studies mathematics. Students still have low understanding of mathematical concepts is caused by the teacher's role in controlling the learning process. Therefore, this research aims to develop Counting Trajectory Learning media (BELITUNG) as a solution to students' problems in learning integers for grade III SD. This research is research and development (Research and Development) with the ADDIE model. Data was obtained by conducting observations, interviews, and questionnaires. After conducting research and development on BELITUNG media, it was found that the score of media experts was 4.1 with a percentage of 82%, and material experts 4.4 with a percentage of 88%. Both stated that this medium was very good. After being tested by experts and revised, then limited trials were carried out on students who were accompanied by the class teacher as expert practitioners. Limited trials get a score of 4.7 percentage 94% if it is converted into qualitative then the media is said to be very good. Based on research and development, it can be concluded that the development of BELITUNG media for learning integers for grade III SD shows that the media is suitable for use in class because it meets very good criteria.